IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING PERSONAL VOCABULARY NOTES TECHNIQUE AT SEVENTH GRADE OF MTS HIFZHIL QURAN MEDAN - Husna, Fauziatul (BRIGHT VISION Journal of Language and Education, 2022)
This research was aimed to find out the improvement of Students’ Vocabulary Mastery by Using Personal Vocabulary Notes Technique which was observed and analyzed from students at seventh grade of MTs Hifzhil Quran Medan. In this research the method applied was the classroom action research. The data of this research was obtained from 38 students and English teacher at MTs Hifzhil Quran Medan. The instrument of collecting the data in quantitative was test and to complete the data qualitative were taken by interview, observation sheets, and documentation. From the result of pre-test, the number of completed are 5 students and the number of uncompleted are 33 students, furthermore the class percentage obtained is 13% which the average value is 63. From the result of posttest I, the number of completed are 16 students and the number of uncompleted are 22 students, furthermore the class percentage obtained is 42% which the average value is 70. From the result of post-test II, the number of completed are 31 students and the number of uncompleted are 7 students, furthermore the class percentage obtained is 81,5% which the average value is 77. It can be concluded that Personal Vocabulary Notes technique can improve students’ vocabulary mastery.